Marketing Strategy Analysis To Increase Consumer Satisfaction Using SWOTAnalysis On Caffein Waroeng Kopi Bojongsari - Fauziah Septiani (Publisher Cv. Inara, 2022)
Marketing has a very important role for trading and service companies. Maintaining excellence, improving service quality by using attractive strategies and appropriate prices in the eyes of consumers is a way to maintain the life cycle of their business. This study aims to determine the marketing strategy in increasing consumer satisfaction using SWOT analysis on Caffeine Waroeng Kopi Bojongsari. This study measures consumer satisfaction with a qualitative method with a phenomenological approach using content analysis and SWOT analysis methods. From the results of the study, the authors carried out a swot analysis by calculating IFAS and EFAS, the recapitulation results obtained that SW = a score of 1.06 and OT = a score of 1.15 this indicates that the company's strategy is in quadrant I. Based on the analysis of strategic factors which can be seen in the SWOT analysis diagram, where Caffeine Waroeng Kopi is in quadrant 1 which shows the SO strategy in the SWOT matrix, namely aggressive strategy. Aggressive strategy is a strategy that uses all strengths to take advantage of opportunities. This strategy is a very profitable strategy because it has opportunities and strengths so that it can be used to progress for Caffeine Waroeng Kopi.